2005
DOI: 10.1366/0003702053946083
|View full text |Cite
|
Sign up to set email alerts
|

Raman Scattering Spectroscopic Study of n-Pentane under High Pressure

Abstract: The Raman spectroscopy of n-pentane was investigated in a Moissanite anvil cell from 0.07 GPa to 4.77 GPa at ambient temperature. The result shows that the CH3 symmetric stretching vibration (2877 cm(-1)) and asymmetric stretching vibration (2964 cm(-1)), the CH2 symmetric stretching vibration (2856 cm(-1)) and asymmetric stretching vibration (2935 cm(-1)), and -(CH2)n- in-phase twist mode (1303 cm(-1)) shifted to higher wavenumbers almost linearly with increasing pressure. Around 2.4 GPa an abrupt visible cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…We will not discuss this transition any further since it has been reported earlier. 1,8,9 In the solid phase, n-pentane crystallizes in an orthorhombic crystal structure with four molecules in the unit cell. 14 The structure of the n-pentane is completely different from other paraffin as the molecular long axes are not parallel to each other.…”
Section: Methodsmentioning
confidence: 99%
“…We will not discuss this transition any further since it has been reported earlier. 1,8,9 In the solid phase, n-pentane crystallizes in an orthorhombic crystal structure with four molecules in the unit cell. 14 The structure of the n-pentane is completely different from other paraffin as the molecular long axes are not parallel to each other.…”
Section: Methodsmentioning
confidence: 99%
“…(six Voigt functions have been used for the fitting procedure of one composite Raman spectrum; see Data ). Individual peaks are recognized at 3034 cm −1 , 2882 cm −1 , 2867 cm −1 , 2856 cm −1 (maximum shift), 2848 cm −1 and 2835 cm −1 , all of them related to C‐H stretching vibrations of CH 3 , CH 2 and CH groups at room temperature and pressure (Qiao & Zheng, ; Yu et al ., ; Shi et al ., ; Kar et al ., ; Behler et al ., ; Hoshina et al ., ).…”
Section: Geochemistry Of Hydrothermal Quartzmentioning
confidence: 99%
“…Presumably this is because some n-pentane remains dissolved in the iso-pentane, thereby raising the freezing pressure of the mixture. No evidence was observed for the potential pressure-induced phase transition of n-pentane in the pressure range of 2.84 to 4.77 GPa reported by Qiao et al, 14 but this may reflect the rather different crystallisation conditions between the two studies.…”
Section: Resultsmentioning
confidence: 70%
“…11 This result is in a good agreement with experimental studies by Reeves et al that extrapolated the freezing pressure of n-pentane to be 1.5 GPa at 298 K. 12 The same study also extrapolated the freezing pressure of iso-pentane to be 2.1 GPa at 298 K. Spectroscopic studies have shown that n-pentane crystallises at ca. 2.5 GPa and 295 K, 13,14 and that there is some evidence for a new high-pressure phase of n-pentane in the pressure range of 2.84 to 4.77 GPa. 14 Based on Raman spectroscopic studies, Williams suggested that the high-pressure crystalline phase of n-pentane crystallises in the orthorhombic crystal system.…”
Section: Introductionmentioning
confidence: 95%